Tathbiq al-Hiwar Litarqiyah Maharah al-Kalam Laday Thullab al-Fashl al-Sani Bi Ma’had ‘Ulum al-Quran Takengon Aceh al-Wustha - Rizka Utami Rizka; Wahyuni Rezeky (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2022)
Speaking skills are one of the competencies taught in Arabic language learning. Students' mastery of Arabic is influenced by various factors during the learning process. Apart from internal factors, there are also external factors that play a significant role in achieving learning objectives. One of the external factors in Arabic language learning is the teaching methods employed in the classroom. The objective of this research is to examine the effectiveness of the á¸¥iwÄr method in enhancing the speaking skills of grade II students at Ulumul Qur'an College Takengon in Central Aceh. This study employed a quantitative research design utilizing quasi-experimental methods. The findings demonstrated that the t-value exceeds the t-critical value; 2.17 2.07. Therefore, the á¸¥iwÄr method is an effective approach to enhance the speaking skills of grade II students at Ulum al-Quran College Takengon. Future research may explore the effectiveness of other teaching methods in improving Arabic speaking skills among students.